PEMANFAATAN ABU SEKAM PADI SEBAGAI SUBSTITUSI PARSIAL SEMEN DALAM PRODUKSI MATERIAL BANGUNAN BERBASIS GREEN CONSTRUCTION - Eddy Elminsyah Jaya (Infratech Building Journal, 2025)
This study aims to examine the utilization of rice husk waste in the form of rice husk ash (RHA) as a partial substitute for cement in the production of building materials based on green construction principles. A quantitative experimental approach was employed through laboratory testing with RHA substitution levels of 0%, 5%, 10%, 15%, and 20% by weight of cement. The parameters evaluated included workability (slump), compressive strength at 7 and 28 days, density, and water absorption. The results indicate that increasing RHA content reduces slump values, reflecting decreased workability. In terms of compressive strength, a decline was observed at 7 days; however, at 28 days, mixtures containing 5% and 10% RHA showed improved strength compared to the control, with the optimum value achieved at 10% RHA (32.8 MPa). Additionally, density decreased while water absorption increased with higher RHA content. Overall, a 10% RHA substitution provides the best balance between mechanical performance and material efficiency. These findings suggest that rice husk ash has strong potential as a sustainable alternative material in environmentally friendly construction practices